Расчет сил резания при торцевом фрезеровании - Розенберг А. М. Александр Минеевич; Куфарев Г. Л. Георгий Леонидович; Розенберг Ю. А. Юрий Александрович; Козлов А. А.; Тахман С. И. (1965, 1965)
Заглавие с титульного листа